Diversity oriented convergent access for collective total synthesis of bioactive multifunctional carbazole alkaloids: synthesis of carbazomycin A, carbazomycin B, hyellazole, chlorohyellazole, and clausenaline D - Markad, Shivaji B.; N. P. Argade (Organic Letters, 2014)
Facile syntheses of imperative carbazole alkaloids carbazomycin A, carbazomycin B, hyellazole, chlorohyellazole, and clausenaline D have been demonstrated starting from readily available Boc-protected 3-formylindole and dimethyl maleate. The suitably substituted aromatic rings have been designed comprising three/four significant C-C bond forming reactions. The competent Wittig reaction, selective monoalkylations, one-pot regioselective Weinreb amide formation and Boc-deprotection, well designed Grignard reactions, dehydrative intramolecular cyclizations, and Baeyer-Villiger rearrangement of aromatic aldehydes were the main features.

Biomimetic collective total synthesis of bioactive carbazole alkaloids indizoline, mafaicheenamine A, claulamine A, claulansine A, and the proposed claulamine E - Markad, Shivaji B.; N. P. Argade (Journal of Organic Chemistry, 2016)
The common precursor 1-methoxy-2-prenyl-3-carbomethoxycarbazole was synthesized from dimethyl indolylmethylenesuccinate in four steps. Well-planned reductive and/or oxidative transformations and intramolecular cyclizations were performed on a pivotal common precursor to accomplish collective first total synthesis of titled natural products and proposed Claulamine E. Burgess reagent induced formation of kinetically controlled product Claulamine A, and intramolecular cyclizations to form bicyclic claulansine A were the key reactions. An alternatively attempted synthesis failed to provide the structural isomer of proposed Claulamine E.

Solid state auto-inversion of C-centrochirality: enantioselective total synthesis of furocarbazolones (-)-epi-claulansine D and (-)-claulansine D and pyranocarbazolone (+)-epi-claulansine C - Markad, Shivaji B.; N. P. Argade (Journal of Organic Chemistry, 2018)
Starting from dimethyl (E)-2-{[(1-tert-butoxycarbonyl)-1H-indol-3-yl]methylene}succinate and (R)-2,2,5,5-tetramethyl-1,3-dioxolane-4-carbaldehyde, facile synthesis of (-)-epi-claulansine D was accomplished via condensation and two intramolecular cyclizations. The (-)-epi-claulansine D in the solid state exists in a metastable form, and after an induction period of 30-90 days, it underwent complete epimerization to exclusively deliver the desired natural product (-)-claulansine D in quantitative yield. The witnessed inversion of C-centrochirality in the solid state is conceptually novel and takes place for relatively higher crystal stability reasons. Base-catalyzed ring expansion of both (+/-)/(-)-epi-claulansine D and (+/-)/(-)-claulansine D resulted in (+/-)/(+)-epi-claulansine C in very good yields.